TMSB10 drives prostate cancer aggressiveness via immune microenvironment regulation - Haoran Xia; Jiaxin Ning; Xiaoxiao Guo; Hongchen Song; Xuanhao Li; Xuan Wang (Molecular Medicine)
Abstract Thymosin β10 (TMSB10) has emerged as a key player in the progression of prostate cancer, significantly influencing the tumor immune microenvironment. Pan-cancer analysis from The Cancer Genome Atlas (TCGA) revealed that TMSB10 is upregulated across multiple cancer types, particularly in prostate cancer, where high TMSB10 expression correlates with poorer patient outcomes. Functional assays using prostate cancer cell lines LNCaP and DU145 showed that TMSB10 silencing suppresses cell proliferation, migration, and invasion, while overexpression enhances these oncogenic processes. Furthermore, co-culture experiments demonstrated that TMSB10 overexpression skews macrophage polarization, decreasing the population of M1-type macrophages while increasing M2-type macrophages. This shift reduces immune cell cytotoxicity and alters cytokine secretion, highlighting TMSB10’s role in immune evasion. These findings establish TMSB10 as a pivotal factor in prostate cancer biology, promoting tumor aggressiveness and modulating the immune response within the tumor microenvironment. TMSB10 presents a promising therapeutic target for prostate cancer, offering new avenues for treatments aimed at altering the tumor immune landscape. This research also provides a foundation for further exploration of TMSB10’s role in other cancers. Graphical abstract